ANALISIS PENGARUH MODAL DAN TENAGA KERJA TERHADAP PRODUKSI KELAPA SAWIT RAKYAT DI KABUPATEN ACEH TAMIANG - Nanda Lisa; Sofyan Syahnur (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
AbstractThis study aims to analyze the effect of capital and labor on people's palm oil production inAceh Tamiang Regency. The method used in this study using the Cobb-Douglas approach whichis a functional form of a broad production function that is used to represent the outputrelationship for input. Data collection used in this study by means of random sampling method.This method uses random or random sample selection. Affecting factors contributing to the production in Aceh Tamiang are capital and labor. The results of the study indicate that the factorsthat influence people's palm oil production in Aceh Tamiang Regency are influenced by capitaland labor. Based on the results of statistical tests obtained using SPSS, it was found that capitaland labor had a positive effect on people's palm oil production in Aceh Tamiang District. It isrecommended that oil palm farmers should utilize KUD optimally so that palm oil products canbe sold at a higher price than the middlemen's selling price, so that the capital and labor usedare more efficient.Keywords: Capital, Labor, Production and Income